Mediasi Motivasi Kerja Hubungan Kompetensi Dalam Meningkatkan Kinerja Pegawai - Ani Setyowati; Moh. Mukhsin; Indra Suhendra; Didit Haryadi (Universitas Bunda Mulia, 2023)
The aspect that can be used as a benchmark for an agency in managing its human resources is employee performance. The purpose of this study, among others, to test and analyze the factors in improving the performance of employees with competence through work motivation. This research was conducted at the Department of Public Works and Spatial Planning with a population of 198 using a sample of 150 respondents. The questionnaire method was distributed using an interval scale of 1 strongly disagree 10 strongly agree. The data analysis technique used SEM PLS. The results of this study indicate the influence of competence on employee performance, the influence of competence on work motivation, the influence of work motivation on employee performance and work motivation can be a mediation in improving employee performance.